Criminalization and Land Rights Conflict: The Indigenous Struggle Against PT Toba Pulp Lestari - Musdodi Frans Jaswin Manalu (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2025)
This study investigates the conflicts between Indigenous Communities and PT Toba Pulp Lestari (TPL) in North Sumatra, focusing on disputes over customary land claims and the criminalisation of indigenous activists. Cases such as the detention of Sorbatua Siallagan illustrate the misuse of power by TPL, often with governmental support. Employing a descriptive qualitative methodology and grounded in Ralf Dahrendorf’s Social Conflict Theory, this research analyses the patterns of conflict, revealing TPL’s monopolistic practices through data manipulation, the use of violence, and the dissemination of propaganda. The findings underscore the necessity of upholding indigenous rights and implementing inclusive policies to achieve sustainable conflict resolution.